Factors contributing to lymph node occult metastasis in supraglottic laryngeal carcinoma cT2-T4 N0M0 and metastasis predictive equation - Ma, Hongzhi; Lian, Meng; Feng, Ling; Li, Pingdong; Hou, Lizhen; Chen, Xiaohong; Huang, Zhigang; Fang, Jugao (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To investigate factors that contribute to lymph node metastasis (LNM) from clinical cT2-T4 N0M0 (cN0) supraglottic laryngeal carcinoma (SLC), and to predict the risk of occult metastasis before surgery. Objective: Methods: A total of 121 patients who received surgery were retrospectively analyzed. Relevant factors regarding cervical LNM were analyzed. Multivariate analyses were conducted to predict the region where the metastasis occurred and prognosis. Results: The overall metastatic rate of cN0 SLC was 28.1%. Metastatic rates were 15.4%, 32.5% and 35.7% for T2, T3 and T4, respectively. Metastatic rates for SLC levels II, III and IV were 19.6%, 17.2% and 3.6%, respectively. A regression equation was formulated to predict the probability of metastasis in cN0 SLC as follows: Pn=e(–3.874+0.749T3+1.154T4+1.935P1+1.750P2)/[1+e(–3.874+0.749T3+1.154T4+1.935P1+1.750P2)]. Approximately 0.2% of patients experienced LNM with no recurrence of laryngeal cancer. Comparison of the intergroup survival curves between patients with and without LNM indicated a statistically significant difference (P=0.029). Conclusions: Cervical lymph node metastatic rates tended to increase in tandem with T stage in patients with LNM in cN0 SLC, and neck dissection is advised for these patients. Moreover, cervical LNM in cN0 SLC showed a sequential pattern and may be predicted.